INTEGRASI SOLAR CELL DAN BATERAI VRLA UNTUK SUMBER ENERGI LISTRIK BERBASIS IoT PADA RUANG FRONT OFFICE KAMPUS POLITEKNIK PIKSI GANESHA - Pebrianti Pramanik, Istitoa; Astriany Rizky, Ardelia; Wirahadi, Umar (INFOKOM (Informatika & Komputer), 2024)
This research presents the implementation of an Internet of Things (IoT) based intelligent system that integrates solar cells and Valve-Regulated Lead-Acid (VRLA) batteries as sources of electrical energy for the front office space at Politeknik PIKSI Ganesha. This system is designed to provide an efficient and environmentally friendly renewable energy solution, while ensuring reliable energy availability. The solar cells function as the main energy collector, while the VRLA batteries act as backup energy storage when sunlight is insufficient. The integration of these two components is managed by a microcontroller connected to the IoT network, enabling remote monitoring and control of the system. This research evaluates the performance and efficiency of the system, as well as explores the potential for its application in other campus environments to support energy-saving efforts and environmental sustainability.